Solitary plasmacytoma of the femur: a case report - Say, Ferhat; Gürler, Deniz; Bülbül, Murat (Ondokuz Mayıs University, 2014)
Solitary plasmacytoma (SP) is a rare type of myeloma which is a hematologic malign tumour originated from plasma cells. It is an isolated tumour which myeloma signs are not observed. SP primarily affects axial skeleton and involvement of extremity is seen rarely. We report a case of SP of proximal femur origin in a 52-year-old woman. The patient was treated with cemented modüler tumour prosthesis following tumour excision. In a one year follow up period, no recurrens or multiple myeloma signs were observed and the patient was able to walk without support and without pain so the treatment resulted successfully.
Keywords: Multiple Myeloma; Plasma Cells; Proximal Femur; Solitary Plasmacytoma